Pengaruh Kualitas Layanan dan Kepercayaan Merek Terhadap Retensi Pelanggan pada CV Yamaha Timbul Jaya Motor Kediri - Yoga Dwi Feriyanto; Tri Yulistyawati Evelina; Rena Feri Wijayanti (INDO PUBLISHING, 2026)
The increasing competition in the motorcycle industry has encouraged companies to enhance their ability to retain customers. Customer retention is influenced by various factors, including service quality and brand trust. This study aims to analyze the effect of service quality and brand trust on customer retention at CV Yamaha Timbul Jaya Motor Kediri. This study employed a quantitative research approach. The population consisted of all customers of CV Yamaha Timbul Jaya Motor Kediri. The sampling technique used was purposive sampling, with a total of 100 respondents. Data were collected through questionnaires, while the data analysis techniques included instrument testing, classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination analysis, and hypothesis testing. The results showed that service quality and brand trust had a very strong relationship with customer retention. The F-test indicated that the calculated F-value was greater than the F-table value (836.319 > 2.70), indicating that service quality and brand trust simultaneously had a significant effect on customer retention. The coefficient of determination (R²) was 0.945, indicating that 94.5% of the variation in customer retention could be explained by service quality and brand trust, while the remaining 5.5% was influenced by other factors not examined in this study. Based on the findings, it can be concluded that service quality and brand trust have a positive and significant effect on customer retention at CV Yamaha Timbul Jaya Motor Kediri. Therefore, the company is advised to continuously improve its service quality by providing responsive, professional, and customer-oriented services, as well as strengthening customers' trust in the Yamaha brand by maintaining consistent product quality and after-sales services to enhance customer retention.